Stability of oil bodies under pulsed electric field exposure to rapeseed: New insights into improving oil extraction capacity - Qiqi Zhang; Jinling Hu; Yunyun Li; Bo Wang; Jing Wang; Jie Zhao; Siming Zhao; Caihua Jia; Jie Kuai; Guangsheng Zhou (Food Chemistry, 2026)

Corrigendum to “Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics” [Food Chem. 513 (2026) 149020] - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Changes in ginseng wine flavor characteristics during fermentation with Saccharomyces cerevisiae - Shen Yao; Yang Li; Xianwei Zeng; Yuan Cui; Zhaolian Li; Meichen Liu; Daqing Zhao; Shiting Yu; Siming Wang (Food Chemistry, 2026)

Hemp seed protein: a promising meat protein substitute with high nutritional value, high safety, and high meat like aroma characteristics - Yuan Cui; Yanling Sun; Yang Li; Weifeng Ni; Zhengqi Dong; Daqing Zhao; Meichen Liu; Weinan Wang; Siming Wang (Food Chemistry, 2026)

Serotonin as a psychosocial biomarker in 3PM psychiatry: from the social brain to personalised intervention - Shengjian Ni; Lixuan Guan; Yuxin Jin; Linjing Liu; Siming Zhu; Wenyang Zhao; Vijayaraj Kumar Palanirajan (EPMA Journal, 2026)

Efficient simulation of landslide-induced surges and control effects of different position piles based on an improved flow-flow model - Zhangqing Wang; Yong Wu; Yongjie Zhao; Yingpeng Wang; Siming He; Xinpo Li; Lei Zhu (Journal of Hydrology, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

A THM-coupled MPM framework for modelling rock-ice avalanches - Xiaoqin Lei; Siming He; Changbing Qin; Jidong Zhao; Gordon G.D. Zhou; Liu Ming (Computers and Geotechnics, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

A hierarchical conflict resolution strategy for collision avoidance in multi-ship encounter scenarios - Ni Shengke; Xian Guoliang; Zhao Zhijie; Wang Xinjian; Liu Guangqiang; Fan Yaxin; Fang Siming (Ocean Engineering, 2025)

Complexes of Dendrobium officinale anthocyanins and polysaccharides: Structural characteristics, stability, antioxidant properties, and bioavailability - Bowen Sui; Yanling Sun; Jingzhi Wang; Yuan Cui; Haibo Xu; Daqing Zhao; Meichen Liu; Zhengqi Dong; Siming Wang; Shichao Liu (Food Bioscience, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

Study on the influence of 3D pre-existing joint on rockfall fragmentation during impact based on discrete element method - Yongjie Zhao; Yong Wu; Yingpeng Wang; Siming He; Xinpo Li; Lei Zhu; Zhangqing Wang (Computers and Geotechnics, 2025)

Decreasing the pH value would improve the swallowing characteristics of whey protein isolate-enriched thickened fluids for dysphagia populations - Zihang Cheng; Kedu Wang; Dongling Qiao; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Incorporating maltitol regulates the gel properties and structural features of κ-carrageenan-corn starch-soy protein isolate based quaternary system and its application of low glycemic index gummies - Xiaowen Pi; Lilin Zhu; Mengqian Xiang; Siming Zhao; Bowen Li; Dongling Qiao; Binjia Zhang (Food Chemistry, 2025)

Germination and fermentation synergistically tailor the starch structure within brown rice and the quality features of brown rice tea - Yabin Guo; Yang Xu; Siming Zhao; Dongling Qiao; Bowen Li; Binjia Zhang (Food Research International, 2025)

Wheat bran insoluble fiber with varying particle distributions orchestrates microbial metabolism to counteract obesity and hyperlipidemia - Kexin Niu; Bingqian Yang; Lu Gan; Meng Niu; Kaikai Li; Siming Zhao (Food Bioscience, 2025)

Polysaccharide–dextrin thickened fluids for individuals with dysphagia: recent advances in flow behaviors and swallowing assessment methods - Kedu Wang; Zihang Cheng; Dongling Qiao; Fengwei Xie; Siming Zhao; Binjia Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Integrative transcriptomic, proteomic and metabolomic analyses yields insights into muscle fiber type in cattle - Xiaofan Tan; Ruixue Zhao; Jing Chen; Zhiwei Yan; Xin Sui; Heling Li; Qiao Li; Xuehai Du; Yangzhi Liu; Siming Yao; Ying Yang; David M. Irwin; et al. (Food Chemistry, 2025)

Swelling than diffusion behavior of starch under protein crowding conditions affects the texture of the protein/starch blend gels - Xuxu Li; Mingcong Fan; Qilin Huang; Siming Zhao; Shanbai Xiong; Dapeng Li (Food Hydrocolloids, 2025)

Acetated starch inclusion to tailor the hierarchical structure and sol-gel features of middle gluten wheat starch-based binary matrices - Bowen Chen; Guojia Jin; Shengsong Ji; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Hydrocolloids, 2025)

Insight of soy protein isolate to decrease the gel properties corn starch based binary system: Rheological and structural investigation - Xiaowen Pi; Lilin Zhu; Mengqian Xiang; Siming Zhao; Zihang Cheng; Dongling Qiao; Binjia Zhang (Food Hydrocolloids, 2025)

Non-local μ(I) rheology improves landslide deposition modeling in MLS-MPM simulations - Shuxi Zhao; Yang Liu; Gianvito Scaringi; Xinpo Li; Siming He; Gang He; Lei Zhu (Engineering Geology, 2025)

The development of thickened fermented rice milk formulation for people with dysphagia: A view of multiple in vitro simulation methods - Zexue Lin; Lingling Ma; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Resolving differences in digestion features of cooked rice and wheat noodles: A view from starch multiscale structure - Zihang Cheng; Siming Zhao; Dongling Qiao; Xiaowen Pi; Binjia Zhang (Food Chemistry, 2025)

Incorporating κ-carrageenan regulates the gel properties and structural characteristics of corn starch-soy protein isolate based ternary system - Zihang Cheng; Mengqian Xiang; Dongling Qiao; Siming Zhao; Xiaowen Pi; Binjia Zhang (Food Hydrocolloids, 2025)

Understanding the application-related features of sweet potato starch varying in multi-scale supramolecular structure - Yabin Guo; Dongling Qiao; Siming Zhao; Xiaowen Pi; Bowen Li; Kai Zhang; Binjia Zhang (Carbohydrate Polymers, 2025)

Analysis of sediment re-formation factors after ginseng beverage clarification based on XGBoost machine learning algorithm - Jiabao Feng; Yuan Cui; Chunyan Jiang; Xueyuan Bai; Daqing Zhao; Meichen Liu; Zhengqi Dong; Shiting Yu; Siming Wang (Food Chemistry, 2025)

Characteristics of Dissolved Inorganic Carbon (DIC) in the Western Coast of the Taiwan Strait Using a Shipboard Measurement - Jiehua Hu; Jinpei Yan; Hang Yang; Siming Huang; Siying Dai; Xiaoke Zhang; Shanshan Wang; Shuhui Zhao (Journal of Marine Science and Engineering, 2024)
An online dissolved inorganic carbon (DIC) monitoring system was produced to achieve high spatial and temporal resolution in DIC data from the western Taiwan Strait (WTS) during the summer. Surface seawater DIC, salinity, dissolved organic carbon (DOC), Chl-a, and NO3− samples were collected, as well as the vertical profiles of DIC, to understand DIC variations in the WTS. The results showed that the range of DIC levels in the surface seawater from the WTS was from 1.68 to 2.21 mmol/L (Mmol), with an average of 1.93 ± 0.19 Mmol, which was consistent with the sampling results using titration determination, with an average of 1.98 ± 0.12 Mmol. A high correlation (R2 = 0.96) was presented between the online monitoring and sampling detection of DIC, indicating that DIC could be measured with high accuracy using the online monitoring system. The spatial distribution of DIC was similar to that of salinity, but it was different from that of DOC and Chl-a. The DIC concentration positively correlated with salinity (R2 = 0.51) and presented a negative correlation (R2 = 0.92) with seawater temperature. However, the surface seawater DIC was almost independent from DOC and Chl-a in the observation sea areas. The DIC levels first increased and then decreased with the depth, with the highest DIC concentration occurring in the subsurface water at about 10 m, which was similar to the profiles of salinity and Chl-a in the northern and southern areas of the WTS. The profiles of DIC, salinity, NO3−, and Chl-a were almost independent from the water depth in the central WST. This indicated that seawater DIC in the WTS was mainly affected by seawater temperature, salinity, and the vertical mixing of sea water, but it was less impacted by TOC and Chl-a.

Untargeted metabolomics to detect and identify plasma metabolic signatures associated with intracranial aneurysm and its rupture - Siming Gui; Jia Jiang; Dingwei Deng; Dachao Wei; Xiheng Chen; Yudi Tang; Jian Lv; Wei You; Ting Chen; Yang Zhao; Hengwei Jin; Xinke Liu; et al. (Metabolic Brain Disease, 2024)

Comparing carbon-saving potential of the pyrolysis of non-recycled municipal plastic waste: Influences of system scales and end products - Bauyrzhan Biakhmetov; Yue Li; Qunshan Zhao; Yong Sik Ok; Abay Dostiyarov; Young-Kwon Park; David Flynn; Siming You (Journal of Cleaner Production, 2024)

Comparison and inhibition mechanism study on the in vitro digestibility of rice starch complex with soy β-conglycinin and soy glycinin - Xin Shi; Xuxu Li; Ruifeng Wang; Meng Niu; Siming Zhao (Food Hydrocolloids, 2024)

Biochar derived from animal and plant facilitates synergistic transformation of heavy metals and phosphorus in sewage sludge composting - Meihua Zhao; Siming Zhong; Xiasong Zhou; Zhen Yu (Environmental Pollution, 2024)

Influence of group VIB metals introduced into zeolite on the adsorption performance of VOCs in cooking oil fumes - Honghong Yi; Siming Guo; Yuting Yuan; Qingjun Yu; Fengshi Meng; Wenjing Wu; Shunzheng Zhao; Ya Wang; Xiaolong Tang (Chemical Engineering Journal, 2024)

Controlling sodium chloride concentration modulates the supramolecular structure and sol features of wheat starch-acetylated starch binary matrix - Shengsong Ji; Siming Zhao; Dongling Qiao; Yan Xu; Caihua Jia; Meng Niu; Binjia Zhang (Carbohydrate Polymers, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Investigating the dynamic process of a rock avalanche through an MLS-MPM simulation incorporated with a nonlocal μ(I) rheology model - Shuxi Zhao; Siming He; Xinpo Li; Gianvito Scaringi; Yang Liu; Yu Deng (Landslides, 2024)

Do E-governance, mineral resources, and policy stringency facilitate economic growth in selected resource-rich countries - Wenjun Wu; Zhilong Zhao; Siming Yu; Minyuan Zhang (Resources Policy, 2024)

Mechanism of the solubility increase of rice protein-ovalbumin co-assembly and its great potential as an emulsifier in high internal phase emulsion - Zufu Song; Siming Zhao; Xiaoli Zhang; Qing Zhang; Yu Han; Meng Niu; Yan Xu (Journal of Cereal Science, 2024)

Ion presence during thermal processing modulates the performance of rice albumin/anthocyanin binary system - Yabin Guo; Ruolan Fang; Yiyuan Zhen; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Research International, 2024)

The influence of biochar from animal and plant on the transformation of phosphorus during paper mill sludge composting - Siming Zhong; Zhen Yu; Xiaoming Liu; Meihua Zhao; Hongwei Rong (Environmental Science and Pollution Research, 2024)

Incorporating edible oil during cooking tailors the microstructure and quality features of brown rice following heat moisture treatment - Yabin Guo; Ruolan Fang; Zhuoting Wu; Gaolei Xi; Dongling Qiao; Genfa Wang; Ting Cui; Liang Zhang; Siming Zhao; Binjia Zhang (Food Research International, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Effect of hydrophobic sucrose esters with different fat acid composition and esterification degree on whipped cream properties - Di Zeng; Yongjian Cai; Tongxun Liu; Lihua Huang; Junwei Wang; Mouming Zhao; Siming Zhu; Qiangzhong Zhao (Food Hydrocolloids, 2024)

Enrichment of resistant starch in starch-protein hydrolysate binary matrix by modulating pH during thermal processing - Cuihong Dai; Zihang Cheng; Yanyu Chen; Dongling Qiao; Gaolei Xi; Qiuling Wang; Fan Zhu; Siming Zhao; Binjia Zhang (Food Research International, 2023)

Study on hydrogenation of oxygenated aromatic hydrocarbons via water-gas shift reaction in a subcritical CO-H2O system - Jiale Gu; Huan Li; Wencai Peng; Di Zhu; Jiajia Chen; Shengjie Luo; Siming Liu; Wenxiang Zhao; Youqing Wu; Sheng Huang; Shiyong Wu (Fuel, 2023)

Ingesting retrograded rice (Oryza sativa) starch relieves high-fat diet induced hyperlipidemia in mice by altering intestinal bacteria - Zihang Cheng; Nannan Li; Zhining Chen; Kaikai Li; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Chemistry, 2023)

Research progress on the adsorption of sulfocompounds in flue gas - Siming Guo; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang; Ya Wang; Yiming Ma; Yuhan Long; Honghong Yi (Chemical Engineering Journal, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Resource curse and green growth in China: Role of energy transitions under COP26 declarations - Siming Yu; Kang Wan; Cheng Cai; Lingli Xu; Tuanjie Zhao (Resources Policy, 2023)

Towards designing dysphagia foods: Recent advances in influencing factors and computer modeling for the swallowing of thickened fluids - Shuhan Liu; Dongling Qiao; Zihang Cheng; Fengwei Xie; Siming Zhao; Binjia Zhang (Trends in Food Science & Technology, 2023)

Incorporating acetylated starch regulates the structure and sol-gel performance of wheat starch-based binary system - Shengsong Ji; Dongling Qiao; Siming Zhao; Yan Xu; Caihua Jia; Meng Niu; Binjia Zhang (Food Hydrocolloids, 2023)

The in-situ dextran produced in rice protein yogurt: Effect on viscosity and structural characteristics - Yu Lu; Caihua Jia; Meng Niu; Yan Xu; Siming Zhao (Carbohydrate Polymers, 2023)

Aspergillus sp. R3, a new producer for cyclopyazonic acid, inhibits rice sheath blight fungus Rhizoctonia solani Kühn - Xiangyu Qin; Yuanhang Chang; Yao Wang; Jie Yang; Siming Nie; Na Guo; Jian Xu; Fengkun Cai; Chunjian Zhao; Yujie Fu (Physiological and Molecular Plant Pathology, 2023)

The differentiation between condensed and hydrolyzable tannins with different molecular weights in affecting the rheological property of wheat flour-based dough - Wenju Ge; Yan Xu; Meng Niu; Caihua Jia; Siming Zhao (Journal of Cereal Science, 2023)

Genetic perturbation of mitochondrial function reveals functional role for specific mitonuclear genes, metabolites, and pathways that regulate lifespan - Cheryl Zi Jin Phua; Xiaqing Zhao; Lesly Turcios-Hernandez; Morrigan McKernan; Morteza Abyadeh; Siming Ma; Daniel Promislow; Matt Kaeberlein; Alaattin Kaya (GeroScience, 2023)
Altered mitochondrial function is tightly linked to lifespan regulation, but underlying mechanisms remain unclear. Here, we report the chronological and replicative lifespan variation across 167 yeast knock-out strains, each lacking a single nuclear-coded mitochondrial gene, including 144 genes with human homologs, many associated with diseases. We dissected the signatures of observed lifespan differences by analyzing profiles of each strain’s proteome, lipidome, and metabolome under fermentative and respiratory culture conditions, which correspond to the metabolic states of replicative and chronologically aging cells, respectively. Examination of the relationships among extended longevity phenotypes, protein, and metabolite levels revealed that although many of these nuclear-encoded mitochondrial genes carry out different functions, their inhibition attenuates a common mechanism that controls cytosolic ribosomal protein abundance, actin dynamics, and proteasome function to regulate lifespan. The principles of lifespan control learned through this work may be applicable to the regulation of lifespan in more complex organisms, since many aspects of mitochondrial function are highly conserved among eukaryotes.

Role of the in-situ-produced dextran by lactic acid bacteria in the texture modification of pea flour pastes - Jike Shuai; Lingyan Zhang; Zhimin Hu; Caihua Jia; Meng Niu; Siming Zhao; Yan Xu (Food Research International, 2023)

Substratum virtualization in three-dimensional landslide modeling with the material point method - Shuxi Zhao; Lei Zhu; Wei Liu; Xinpo Li; Siming He; Gianvito Scaringi; Xiong Tang; Yang Liu (Engineering Geology, 2023)

Global DNA and protein interactomes of FLT1P1 (Fms-related tyrosine kinase 1 pseudogene 1) revealed its molecular regulatory functions associated with preeclampsia - Lu Zhao; Siming Xin; Yunfei Wu; Shaofang Huang; Kangxiang Xu; Yuqi Xu; Dong Ruan; Bingqi Wu; Dong Chen; Xiaoju He (Molecular Biology Reports, 2023)

Correction to: Stress and load-bearing structure analysis of the surrounding rock in a soft broken roadway - Guangming Zhao; Chongyan Liu; Siming Kao; Xiaobo Zhang; Xiang Cheng (Arabian Journal of Geosciences, 2020)

Stress and load-bearing structure analysis of the surrounding rock in a soft broken roadway - Guangming Zhao; Chongyan Liu; Siming Kao; Xiaobo Zhang; Xiang Cheng (Arabian Journal of Geosciences, 2020)

Photocatalytic removal of elemental mercury via Ce-doped TiO2 catalyst coupling with a novel optical fiber monolith reactor - Feng Xin; Siming Ma; Jianping Yang; Yongchun Zhao; Junying Zhang; Chuguang Zheng (Environmental Science and Pollution Research, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Emission controls of mercury and other trace elements during coal combustion in China: a review - Yongchun Zhao; Jianping Yang; Siming Ma; Shibo Zhang; Huan Liu; Bengen Gong; Junying Zhang; Chuguang Zheng (International Geology Review, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

Molecular cloning, recombinant expression, and antifungal functional characterization of the lipid transfer protein from Panax ginseng - Kexin Cai; Jiawen Wang; Min Wang; Hui Zhang; Siming Wang; Yu Zhao (Biotechnology Letters, 2016)

Comparative analysis of differentially expressed genes in Sika deer antler at different stages - Yu Zhao; Baojin Yao; Mei Zhang; Siming Wang; Hui Zhang; Wei Xiao (Molecular Biology Reports, 2013)

Antibody-Mediated Inhibition of Integrin α5β1 Blocks Neurotoxic Prion Peptide PrP106–126-Induced Activation of BV2 Microglia - Jiaxin Chang; Lifeng Yang; Mohammed Kouadir; Yun Peng; Siming Zhang; Fushan Shi; Xiangmei Zhou; Xiaomin Yin; Deming Zhao (Journal of Molecular Neuroscience, 2012)